2021
DOI: 10.1177/0898010120983659
|View full text |Cite|
|
Sign up to set email alerts
|

Alternate Nostril Breathing to Reduce Stress: An Option for Pregnant Women Survivors of Intimate Partner Violence?

Abstract: Background: Stress resulting from intimate partner violence (IPV) on pregnant women causes and sustains poor health and contributes to poor pregnancy and birth outcomes. Appropriate interventions to reduce stress in this population of women are warranted. Objective: To present a systematic review and the state of the science of evidence on alternate nostril breathing (ANB) as a holistic intervention for stress reduction for pregnant survivors of IPV, framed by complex adaptive systems theory and psychoneuroimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
(219 reference statements)
1
5
0
Order By: Relevance
“…ANB can help reduce the risk of cardiorespiratory complications by acting upon the effector organs, i. e. lungs and heart. (14,15,16) Data analysis suggests that regular practice of ANB improves the respiratory endurance and capacity in individuals, evidenced by the significant increase in FVC, FEV1, and PEFR from their baseline values, ultimately contributing to a reduction in risk and compli-cations in pulmonary and cardiovascular disorders (17,18). The increase in FVC might be the strengthening of respiratory muscles by regular practice of breathing exercises.…”
Section: Discussionmentioning
confidence: 99%
“…ANB can help reduce the risk of cardiorespiratory complications by acting upon the effector organs, i. e. lungs and heart. (14,15,16) Data analysis suggests that regular practice of ANB improves the respiratory endurance and capacity in individuals, evidenced by the significant increase in FVC, FEV1, and PEFR from their baseline values, ultimately contributing to a reduction in risk and compli-cations in pulmonary and cardiovascular disorders (17,18). The increase in FVC might be the strengthening of respiratory muscles by regular practice of breathing exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Our search strategy incorporated PubMed and ScienceDirect electronic searches (Appendix A.1) and manual reference-mining of previously published reviews and key clinical trials [22][23][24][25]33,[35][36][37][38][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Search Strategymentioning
confidence: 99%
“…Previous reviews have provided insight into the psychological and/or physiological benefits of slow breathing [52], diaphragmatic breathing [36], ANB [38], and other breath practices [23,25,35,37]. While these studies have examined a range of populations, their selection criteria have precluded more nuanced analyses.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies examining the anti-hypertensive effect of Yoga. [18] , [19] , [20] , [21] The effect of breathing exercises is not limited to controlling BP and HR but can also lead to an improvement in anxiety, 22 , 23 depression, 24 pain perception, 25 chronic obstructive pulmonary disease, 26 asthma, 27 insomnia, 28 stress, 29 PTSD, 30 and cancer. 31 Although multiple studies have reported a positive effect of breathing exercises on reducing BP [ [32] , [33] , [34] ] and HR, 32 there is no pooled data concluding this individual component of yoga leads to a decrease in BP and HR.…”
Section: Introductionmentioning
confidence: 99%